Food and nutrition security: Role of state support policies in Odisha. Issue 1 (12th August 2020) - Sahoo, Malayaranjan
Abstract : This study focuses on Food and nutrition security in Odisha and specifically survey the contribution of PDS and ICDS on food and nutrition security in the NAGADA village of Jajpur district of Odisha. The whole study is based upon descriptive and qualitative in nature. This analysis is based on the source of both primary and secondary data. The main tool for data collections are the interview schedule from the Nagada village (Odisha, India). The interview schedules contained mostly close ended questions, though some open ended and structure questions also administered. It is found that most of the people in that village depend on PDS. ICDS scheme is not functioning in the study village. For impact of socio‐economic parameter on health status, we got education of the households, female education, MPCE and casual labors show significant relation, whereas household size display negative and case and land own do not show any relation with health status.